SOD1 Deficiency Reveals Indirect Redox Stress Mechanisms Underlying Vanillin Toxicity in Saccharomyces cerevisiae Yeast - Sabina Bednarska; Magdalena Kwolek-Mirek; Roman Maslanka; Dominika Graboś; Gabriela Świniuch; Renata Zadrag-Tecza (Antioxidants)
Vanillin is a compound of great utility, and its production is, among others, based on using microorganisms such as Saccharomyces cerevisiae yeast. The effect of vanillin on cells is not fully understood. It has been demonstrated that vanillin induces oxidative stress; however, evidence also suggests its beneficial effects, including antioxidant and anti-inflammatory properties. For this reason, the present study was designed to elucidate the mechanism of vanillin’s action and to ascertain the extent to which its toxic effect is attributable to oxidative stress. The studies were conducted using wild-type and Δsod1 mutant strains. SOD1 deficiency results in cell hypersensitivity to oxidative factors, thus making the mutant strain a valuable model for investigating various aspects of oxidative stress. Based on an evaluation of cell vitality, Yap1p activation, ROS content, and glutathione and NADP(H) content, it can be concluded that oxidative stress is a secondary effect of metabolic and redox perturbations in cells rather than a direct consequence of vanillin reactivity. Furthermore, alterations observed in the redox couples GSH/GSSG and NADPH/NADP+ are one of the reasons for oxidative stress and suggest that vanillin may induce the utilization of NADPH for cellular needs other than antioxidant effects.